Clinical fractures of veneered zirconia single crowns - De Almeida Jr., Antonio Alves; Chavez, Oscar Fernando Munoz; Galvao, Beatriz Regalado; Adabo, Gelson Luis [UNESP] (My University, 2013)
Crowns made from an yttria-stabilized tetragonal zirconia polycrystals (3Y-TZP) core with a porcelain veneer have shown high clinical failure rates. Manifestations of clinical failure in veneering ceramic ranges from a single chip to an extended fracture. Core failures are uncommon but usually are catastrophic. This article examines the possible causes of failure in zirconia systems and presents a case report involving the diagnosis and repair of three different types of failure in six 3Y-TZP/porcelain crowns.
Keywords: Crowns; Dental porcelain; Dental restoration; Dental restoration failure; Human; Zirconium